Self-Control in Patients with Drug Addiction - Jannah, Firdausil (Universitas Negeri Surabaya, 2023)
The results showed that the subject used drugs from adolescence to the beginning of college and continued to use drugs so that he became addicted. The thing that underlies the subject's behavioral control not to return to being a drug addict is the desire not to disappoint parents. In cognitive control, subjects know the negative effects of drugs through various sources and realize the impact they feel. Subjects tried to assess the events they experienced from a positive perspective. In decision control, the subject chose to distract themselves from thoughts of wanting to use drugs and by thinking about their future. While in relapse, the three subjects experienced relapse after leaving the rehabilitation center with different factors, such as social support, family, and the wrong time and place.